Postgraduate Students' Perceptions Of Using The Zoom Application In EFL Online Class - NINGSIH, FITRI RANDIA; Dewi, Utami; Daulay, Sholihatul Hamidah (Language Circle: Journal of Language and Literature, 2023)
Impactful features of the COVID-19 pandemic have brought many sectors, particularly the educational one. Online learning has replaced traditional classroom instruction. It puts a strain on both the students and the teachers to fully support the success of the online sessions. In order to effectively communicate learning materials to their students, teachers must use more creativity. Students are encouraged to be independent learners in the meanwhile. Therefore, this article aims to ascertain students' perceptions about applying the ZOOM program to facilitate online learning and examine how this application is reshaping the educational sector. This study used a descriptive qualitative method. The data was obtained from the questionnaire via Google form. The participants of this research were 20 postgraduates in English Education at one of the universities in Indonesia.